Strengthening Environmental Awareness Through the Implementation of the Love Curriculum in Madrasahs - Abdi Syahrial Harahap (Hikmah, 2025)
This study aims to analyse the strengthening of environmental awareness through the implementation of the Love Curriculum at MAS Tahfizhil Qur'an Islamic Centre as a model of character education based on Islamic values. This study uses a qualitative method with a case study approach. Data was obtained through in-depth interviews, participatory observation, and documentation, then analysed interactively with triangulation of sources and techniques to ensure validity. The results show that the Love Curriculum is effective in fostering ecological awareness among students through the integration of religious, moral, and ecological values in learning activities and school culture. The values of love for Allah, others, and nature are internalised through habit formation, role modelling, and practical activities such as waste management and recycling. Despite limitations in facilities and behavioural consistency, this curriculum successfully shapes positive ecological behaviour and spiritual awareness that caring for nature is a religious duty. Theoretically, this research enriches the concept of eco-spiritual character education that combines faith and ecological responsibility, while practically serving as a reference for Islamic educational institutions in developing love-based and environmentally sustainable curricula.